A Unpacking Music Video Production Practices: Case Study: “Hollow” by Breacheven - Muhammad Riffat Alfito; Khaerudin Imawan; Aghnia Dian Lestari (Indonesian Journal Publisher, 2026)
This study aims to analyze broadcasting production practices in the creation of the music video “Hollow” by the indie band Breacheven, which was independently produced using a do-it-yourself (DIY) approach. This research employs a qualitative descriptive methodology, utilizing in-depth interviews with the director and the band’s vocalist, along with an analysis of the audiovisual production process. The findings indicate that the production of the “Hollow” music video is not merely a technical activity, but a social and cultural practice that reflects values of independence, work flexibility, and the collective identity of indie musicians. During the production stage, broadcasting elements such as cinematography, lighting, and editing were applied adaptively by optimizing available resources, accompanied by meaning negotiation between the band and the director in developing the visual concept. Distribution was carried out through digital platforms, particularly YouTube and Instagram, representing decentralized broadcasting practices that enable independent dissemination without reliance on conventional media institutions. In terms of consumption, audiences were not positioned as indicators of commercial success, but rather as interpretative spaces for meaning-making and visual identity formation. This study concludes that independent broadcasting production through a DIY approach can serve as an effective strategy for local indie bands to enhance visual quality, maintain creative autonomy, and strengthen their presence within the digital music industry.